Determination of the Performance of Cookstoves Using the Controlled Cooking Test: Benin Case Study - HOUNGAN, COMLAN ARISTIDE; AWANTO, Christophe; ANJORIN, MALAHIMI (My University, 2014)
Biomass cook stoves are widely used in developing countries. These stoves generally use wood fuel which represents about 60 to 86% of the total primary energy consumption in Africa; a few exceptions are observed in northern Africa countries and South Africa where this rate is lower. For some African regions, this rate raises up to 90-98% of the total consumption. In Benin, the estimations of the june 1993 environmental action plan reveal that the forest declines in area by 100 thousand hectares every year. The purpose of this study is to evaluate the influence of the type of meal and the type of stove on its performances.
Keywords: Energy; Renewable Energy Sources; Efficiency; Measurement techniques; Weight measurement; distance measurement; current measurement; Calorimetry; Economics indicators; Environmental economic.